2015
DOI: 10.1016/j.clgc.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Combining Immunotherapy and Radiation for Prostate Cancer

Abstract: Radiotherapy has conventionally been viewed as immunosuppressive, which has precluded its use in combination with immunotherapy for prostate and other cancers. However, the relationship between ionizing radiation and immune reactivity is now known to be more complex than was previously thought, and data on the use of radiotherapy and immunotherapy are accumulating. Herein, we review this topic in the light of recently available data in the prostate cancer setting. Recent research has shown no significant lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…There are several unanswered questions that are being investigated to determine how to induce the native immune system to recognize and attack metastatic tumor cells, including the optimal fractionation size of local radiotherapy to induce tumor antigen expression, the timing of delivery of radiotherapy in conjunction with immunotherapy [6-7], and which drug therapies show the best promise in priming the immune system [8-10]. …”
Section: Discussionmentioning
confidence: 99%
“…There are several unanswered questions that are being investigated to determine how to induce the native immune system to recognize and attack metastatic tumor cells, including the optimal fractionation size of local radiotherapy to induce tumor antigen expression, the timing of delivery of radiotherapy in conjunction with immunotherapy [6-7], and which drug therapies show the best promise in priming the immune system [8-10]. …”
Section: Discussionmentioning
confidence: 99%
“…The goal is to modify the phenotype of cancer cells, making it easier for immune cells to recognize and kill them (37). …”
Section: Experimental Prostate Cancer Vaccinesmentioning
confidence: 99%
“…6,21 Recent studies have indicated that combining immunotherapy with chemotherapy, radiotherapy, or both is an effective method of prolonging patient survival and enhancing immunological responses. [22][23][24] In addition, the other study reported an immunotherapeutic strategy that combined an autologous tumor lysate-loaded DC vaccine with CIK and NK cells to treat undifferentiated embryonal sarcoma of the liver, 23 which is a rare but rapidly growing malignant spindle cell tumor, with satisfactory outcomes. 25 All these previously reported cases relieved the tumor progression and prolonged the lives of the patients; however, to our knowledge, no patients experienced pathologic remission (clinical cure).…”
Section: Discussionmentioning
confidence: 99%